THE EFFECT OF ADDITIONAL SALT AND ACID ON THE HYDROPHOBIC LAYER OF NANOCOMPOSITE SILICA/POLYSTYRENE (SiO2/PS) ON THE STABILITY PROPERTIES OF UV - Yola sri Wahyuni; - Ratnawulan (Department of Physics – Universitas Negeri Padang UNP, 2021)
In nature there is a phenomenon. Which this phenomenon can be seen in the lotus leaf and taro leaves. a phenomenon called hydropobic (water repellent) properties. This research is a previous research. On application, the hydrophobic coating will mostly break down quickly when applied outside or in harsh environments. So it is very important to develop a durable hydrophobic layer, especially the stability properties against Ultra Violet (Uv). Therefore, this study aims to see the effect of adding salt and acid to the hydrophobic silica / polystyrene nanocomposite (SiO2 / PS) layer on the stability of the Uv. with a polystyrene composition of 0.5 grams and 0.2 grams of silica powder and 0.4 grams of salt and 0.4 grams of acid. The coating method used is the spin coating method and the Uv stability test on the hydrophobic layer is done by drying the layers for one hour under direct sunlight. The results of this study were the contact angle measurements using imagej software, and the crystal grain size by SEM (Scanning electron microscop). UV stability can be seen by changing the contact angle in each sample where the contact angle that can be before irradiation is acid added salt (120.1490C), salt (100.3630C), acid (128.5910C), without mixture (133.6680C) ) and after irradiation is. Salt (92.970C), unmixed (98.1440C), acid added salt (92.1150C), acid (141.5750C). These results may indicate that acid coating is more likely to use hydrophobic / self-cleaning surfaces in harsh environments such as high Uv irradiation, and outdoor applications.